Gender Based Differences in Business Model, Online Community Participation and Period of Becoming Entrepreneur in Relation to Product Creativity and Social Marketing - Tuti, Meylani; Syarief, Rizal; Anggraeni, Elisa; Rochman, Nurul Taufiqu (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 16 Nomor 2 Tahun 2022DO - 10.24843/MATRIK:JMBK.2022.v16.i02.p01, 2022)
Becoming an entrepreneur is one of the opportunities for today's young generation, especially during a pandemic that causes them to lose their jobs. Efforts made by the government to facilitate the emergence of an entrepreneurial spirit are in the form of financial assistance and coaching needed by new entrepreneurs. This study observed three variables that can improve entrepreneurs' business performance: business models, marketing through social media, and product creativity. The three variables are distinguished by gender, membership in online communities, and period of being a food entrepreneur. The study results indicate differences between men and women in the business model and product creativity variables and their online food entrepreneurship community participation. However, there is no difference between men and women as community members on social media marketing.